Cloud Cost Management for Startups : Strategies for Success - Shahnawaz Khan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This research article explores the critical importance of cloud cost management for startups, presenting a comprehensive analysis of both successful strategies and cautionary tales. As cloud computing becomes increasingly integral to startup operations, the challenge of managing associated costs effectively has emerged as a key factor in determining long-term success. Through case studies of companies like TechNova and FinEdge, the article highlights successful approaches such as automation-driven optimization and the adoption of FinOps culture. Conversely, it examines the pitfalls of poor cost management practices through the experiences of E-Commerce Express and SwiftApp. The study identifies five key strategies for effective cloud cost management: early implementation of automation, adoption of a FinOps culture, continuous monitoring of cloud usage, regular right-sizing of resources, and planning for scalability. By providing actionable insights and quantitative data on the impact of these strategies, this article aims to equip startup leaders with the knowledge to optimize their cloud expenditure while maintaining the agility and scalability necessary for growth in competitive markets.